External validity and anchoring heuristics: application of DUNDRUM-1 to secure service gatekeeping in South Wales. (30th January 2018) - Lawrence, Daniel; Davies, Tracey-Lee; Bagshaw, Ruth; Hewlett, Paul; Taylor, Pamela; Watt, Andrew
Abstract : Aims and method: Structured clinical judgement tools provide scope for the standardisation of forensic service gatekeeping and also allow identification of heuristics in this decision process. The DUNDRUM-1 triage tool was completed retrospectively for 121 first-time referrals to forensic services in South Wales. Fifty were admitted to medium security, 49 to low security and 22 remained in open conditions. Results: DUNDRUM-1 total scores differed appropriately between different levels of security. However, regression revealed heuristic anchoring on the 'legal process' and 'immediacy of risk due to mental disorder' items. Clinical implications: Patient placement was broadly aligned with DUNDRUM-1 recommendations. However, not all triage items informed gatekeeping decisions. It remains to be seen whether decisions anchored in this way are effective. Declaration of interest: Dr Mark Freestone gave permission for AUC values from Freestone et al . (2015) to be presented here for comparison.